Numerical models for the dynamic response of submerged floating tunnels under seismic loading. - Di Pilato, Mariagrazia
The modeling of tethering elements of seabed anchored floating structures is addressed, with particular reference to the so-called Archimedes Bridge (submerged floating tunnel, SFT) solution for deep water crossing; attention is devoted to the design solution encompassing slender bars as anchor elements. Two numerical tools are proposed: firstly, a geometrically nonlinear finite element (NWB model), developed in previous work, has been refined in order to capture the effect of higher flexural modes of anchor bars. Secondly, a 3D beam element, based on the classical corotational formulation (CR model), has been developed and coded. Both elements are implemented in a numerical procedure for the dynamic time domain step-by-step analysis of nonlinear discretized systems; seismic loading is introduced by generating artificial time histories of spatially variable seismic motion. An example of application of the NWB element is shown regarding the behavior of the dynamic model of a complete SFT. The model was subjected to extreme multiple-support seismic loading. The seismic behavior is here illustrated and commented, especially in light of the effect of higher local vibration modes of the anchor bars. Finally, a comparison between the performances of the two modeling approaches is presented. Both harmonic and seismic excitations are considered in the test; the results justify the use of the simpler NWB approach, especially in the SFT design phase.
Keywords: Nonlinear dynamics; Geometrical effects; Multiple-support seismic excitation